Caring for the health and well-being of our learners in medicine as critical actions toward high-quality care - Orit Karnieli-Miller (BMC, 2022)
Abstract A recent paper has focused on residents' poor lifestyle habits and their potential negative impact on patients' lifestyles. This commentary argues that there are even greater reasons to be concerned about the health and well-being of residents and medical students and the resultant effects on patients throughout the careers of these learners. There is a "hidden curriculum", i.e., customs, rituals and norms of behavior, in medical education and in the training at the healthcare setting, often contradicts the formal curriculum and include messages that neglect the basic needs of the learners as well as the patients. Due to the impact of these messages on the professional identity formation of learners, including a deterioration in their own wellbeing as well as impairment of their ability to empathize with and care for patients, we must align our formal and hidden curricula to show dignity and caring for learners, colleagues, and patients. To do this well, we need to change our approach. We need to add processes for learners to support them in dealing with the stresses of their education and training and allow them to build their families and commit fully to medicine as a vocation, not just a job. We also must add faculty development processes to help align the formal and hidden curricula and help faculty empower and constructively assist their learners to handle challenging situations, e.g., where they see a resident struggling with patient care and day-to-day workload, through empathic feedback. When our learners are treated with kindness and respect they will lead more fulfilling lives and be better able to provide the high-quality care and caring all patients deserve.